Strategi Pemberdayaan UMKM Produk Kacang Mete melalui Inbound Marketing Berbasis Internet di Kecamatan Jatisrono, Kabupaten Wonogiri (Studi Kasus di Klaster Giri Jaya Mete) - Grace Nanda Priasti; Sapja Anantanyu; Putri Permatasari (Universitas Sebelas Maret, 2022)
Digital marketing innovation makes entrepreneurs try to implement product marketing through the internet. Micro, small and medium enterprises (MSME) actors as agricultural business actors are expected to improve the quality of human resources and the quality of their products so that marketing can be managed independently and increase the product's selling value. This research discusses the determination of strategies for empowering MSME actors to take advantage of digital technology through internet-based inbound marketing. The purpose of the study was to formulate an alternative strategy for empowering MSMEs cashew nuts in the Giri Jaya Cashew Cluster in conducting inbound marketing. This research is a type of case study research. The basic research method used is a qualitative descriptive method. The research location is Tanjungsari Village, Jatisrono Sub-district, in the Giri Jaya Mete Cluster. Research informants are the secretary of FEDEP (Forum for Economic Development and Employment Promotion), field extension agents for Cooperatives, MSMEs, Industry and Trade, Head of Community Empowerment Division of the Jatisrono Sub-district Government and community entrepreneurs of MSMEs cashew nut products. The data analysis technique used is through three stages of determining informants, namely the input stage (environmental analysis and IFAS-EFAS analysis), the matching stage (SWOT matrix analysis) and decision making (QSPM matrix analysis). Cashew nut MSMEs in Jatisrono Sub-district are in quadrant I position, meaning that cashew nut MSMEs have a lot of internal strength and many opportunities from outside. The strategy that must be applied in this condition is to support an aggressive growth policy (growth oriented strategy). The right alternative strategy is to combine aspects of digital marketing such as content marketing, blogs, search engine optimization, social media marketing and branding with community empowerment such as training, demonstrations and mentoring.